Hubungan Terpaan Tweet “Twitter, Please Do Your Magic” dengan Sikap Remaja - Alya Ratna Dewi; Dadi Ahmadi (Jurnal Riset Public Relations, 2022)
Abstract. Twitter as microblogging is a popular form of short blog offers a variety of new information quickly through short messages that someone shares through the timeline. The appearance of the phrase "Twitter, Please Do Your Magic" which is used to share problems with people, contains the hope that the problem can be resolved quickly through the help of retweets, retweet quotes (replies). Based on this phenomenon, the purpose of the study was to find out how the relationship between the exposure of "Twitter, Please Do Your Magic" tweets and adolescent attitudes. Researchers use quantitative methods with correlational analysis techniques. The population in this study was the followers of The Coil Twitter account numbering 793,400 followers. With the sampling technique using simple random sampling obtained the number of research samples as many as 60 Twitter users who responded to one of the tweets "Twitter, Please Do Your Magic on @Kumparan account. The data collection techniques used in this study are questionnaires, observations, and literature studies. The data analysis techniques used in this study are descriptive technical analysis and inferential analysis techniques. The results showed that there was a significant and significant relationship between the tweet "Twitter, Please Do Your Magic" and adolescent attitudes. Abstrak. Twitter sebagai microblogging yaitu bentuk blog singkat populer menawarkan beragam informasi baru secara cepat melalui pesan-pesan singkat yang dibagikan seseorang melalui timeline. Kemunculan kalimat “Twitter, Please Do Your Magic” yang digunakan untuk membagikan permasalahan seesorang, mengandung harapan agar permasalahan tersebut dapat terselesaikan dengan cepat melalui bantuan retweet, quote retweet (reply). Berdasarkan fenomena tersebut maka tujuan dari penelitian ini adalah untuk mengetahui bagaimana hubungan antara terpaan tweet “Twitter, Please Do Your Magic” dengan sikap remaja. Peneliti menggunakan metode kuantitatif dengan teknik analisis korelasional. Populasi dalam penelitian ini adalah followers akun Twitter Kumparan berjumlah 793.400 followers. Dengan teknik pengambilan sampel menggunakan simple random sampling diperoleh jumlah sampel penelitian sebanyak 60 pengguna Twitter yang merespon salah satu tweet “Twitter, Please Do Your Magic di akun @Kumparan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner, observasi, dan studi pustaka. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis deskriptif dan teknik analisis inferensial. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan dan cukup berarti antara terpaan tweet “Twitter, Please Do Your Magic” dengan Sikap Remaja.